The Role of Semaphorins and Their Receptors in Gliomas - Law, Janice Wai Sze (Hindawi Publishing Corporation, 2012)
Gliomas are the most common tumor in the central nervous system. High-grade glioblastomas are characterized by their high invasiveness and resistance to radiotherapy, leading to high recurrence rate and short median survival despite radical surgical resection. Characterizations of gliomas at molecular level have revealed aberrations of various growth factor receptors, receptor tyrosine kinases, and tumor suppressor genes that lead to deregulation of multiple signaling pathways, thereby contributing to abnormal proliferation, invasion, and resistance to apoptosis in cancer cells. Recently, accumulating evidence points to the emerging role of axon guidance molecules in glioma progression. Notably, many signaling events harnessed by guidance molecules to regulate cell migration and axon navigation during development are also found to be involved in the modulation of deregulated pathways in gliomas. This paper focused on the signalings triggered by the guidance molecule semaphorins and their receptors plexins and neuropilins, and how their crosstalk with oncogenic pathways in gliomas might modulate cancer progression. The emerging role of semaphorins and plexins as tumor suppressors or oncogenes is also discussed.